Acorda fogueteiro, pisa pólvora no ar, buscapé, barco de fogo, o forró vai começar: o ensino de história à luz do barco de fogo e dos fogos de artifício nos festejos juninos de Estância/SE - Santos, José Marcelo Araújo (2025)
Festivals in Brazil are an essential part of social life. With the arrival of the Portuguese, European culture was influenced by Indigenous and African traditions, resulting in a diverse and plural identity. In a country of continental dimensions, each region developed its own traditions, strengthening feelings of belonging and identity. In the Northeast, the June festivals stand out as the main annual celebration. In Estância, Sergipe, beyond the festivities, the city is distinguished by the production of fireworks, such as buscapé and espada, and by the Barco de Fogo, a genuinely Estanciano June artifact that captivates residents and tourists with a spectacle of colors and sounds. Recognized as intangible heritage, the Barco de Fogo holds great cultural and economic significance for the municipality. Thus, the objectives of this study were to contribute to the appreciation of the city's June culture, analyze how fireworks and the Barco de Fogo can be used in History teaching, and promote learning focused on the specificities of individuals and the interests of the school community. The study aimed to highlight the local June culture and explore how fireworks can be integrated into History education, fostering meaningful learning connected to identity and collective memory. Based on dialogue with Pierre Nora, Maurice Halbwachs, Sandra Pelegrini, among others, the research resulted in an open educational resource (OER): a collaboratively created sticker album in which teachers and students can engage with memory, artistic and cultural expressions, and local identities.